Attention-deficit/hyperactivity disorder in elite athletes: a narrative review. Issue 12 (8th June 2019) - Han, Doug Hyun; McDuff, David; Thompson, Donald; Hitchcock, Mary E; Reardon, Claudia L; Hainline, Brian
Abstract : Attention-deficit/hyperactivity disorder (ADHD) is a common brain developmental disorder in the general population that may be even more prevalent in elite athletes in certain sports. General population studies of ADHD are extensive and have reported on prevalence, symptoms, therapeutic and adverse effects of treatment and new clinical and research findings. However, few studies have reported on prevalence, symptoms and treatments of ADHD in elite athletes. This narrative review summarises the literature on symptoms, comorbidities, effects of ADHD on performance and management options for elite athletes with ADHD. The prevalence of ADHD in student athletes and elite athletes may be 7%–8%. The symptoms and characteristics of ADHD play a role in athletes' choice of a sport career and further achieving elite status. Proper management of ADHD in elite athletes is important for safety and performance, and options include pharmacologic and psychosocial treatments.